2017
DOI: 10.1038/s41598-017-02556-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulatory role of sound vibration treatment in Arabidopsis thaliana against Botrytis cinerea infection

Abstract: Sound vibration (SV), a mechanical stimulus, can trigger various molecular and physiological changes in plants like gene expression, hormonal modulation, induced antioxidant activity and calcium spiking. It also alters the seed germination and growth of plants. In this study, we investigated the effects of SV on the resistance of Arabidopsis thaliana against Botrytis cinerea infection. The microarray analysis was performed on infected Arabidopsis plants pre-exposed to SV of 1000 Hertz with 100 decibels. Broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 62 publications
2
53
0
Order By: Relevance
“…Our previous GO analysis of transcriptomics data also revealed that differentially expressed genes in the SV-infected plants were enriched with various primary metabolic processes (Choi et al, 2017). For example, the upregulated genes at 12 hpi in the SV-infected plants were enriched with redox homeostasis (GO:0045454) function.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous GO analysis of transcriptomics data also revealed that differentially expressed genes in the SV-infected plants were enriched with various primary metabolic processes (Choi et al, 2017). For example, the upregulated genes at 12 hpi in the SV-infected plants were enriched with redox homeostasis (GO:0045454) function.…”
Section: Resultsmentioning
confidence: 95%
“…In our previous study, we observed significant differences in disease level between SV-infected and non-SV–infected plants at 72 hpi, i.e ., non-SV–infected plants had more senescent leaves than SV-infected plants (Choi et al, 2017). We observed similar results in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations